2016
DOI: 10.1021/acs.chemmater.6b01329
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Lead-Free and Stable Perovskite Derivative Cs2SnI6 Nanocrystals via a Facile Hot-Injection Process

Abstract: Colloidal nanocrystals of lead halide perovskites have recently received great attention due to their remarkable performance in optoelectronic applications (e.g., light-emitting devices, flexible electronics, and photodetectors). However, the use of lead remains of great concern due to its toxicity and bioaccumulation in the ecosystem; herein we report a strategy to address this issue by using tetravalent tin (Sn 4+ ) instead of divalent lead (Pb 2+ ) to synthesize stable Cs 2 SnI 6 perovskite nanocrystals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
336
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(357 citation statements)
references
References 52 publications
12
336
0
9
Order By: Relevance
“…[111] Cs 2 AgBiBr 6 NCs were achieved by injecting Csoleate at 200 °C into a high boiling organic solvent containing BiBr 3 and AgNO 3 . [112] It involved a reaction at 220 °C and in ambient between Cs-oleate and tin(IV) iodide in the presence of oleylamine and oleic acid using octadecane as the solvent. The quality of Cs 2 AgBiBr 6 NCs could be improved by a deliberate control of the HBr and oleic acid/oleylamine (OA/ OLA) additives and the reaction temperature.…”
Section: Materials Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…[111] Cs 2 AgBiBr 6 NCs were achieved by injecting Csoleate at 200 °C into a high boiling organic solvent containing BiBr 3 and AgNO 3 . [112] It involved a reaction at 220 °C and in ambient between Cs-oleate and tin(IV) iodide in the presence of oleylamine and oleic acid using octadecane as the solvent. The quality of Cs 2 AgBiBr 6 NCs could be improved by a deliberate control of the HBr and oleic acid/oleylamine (OA/ OLA) additives and the reaction temperature.…”
Section: Materials Synthesismentioning
confidence: 99%
“…Their crystal structure is depicted by Maughan et al, as shown in Figure 9a,b. Although there are some conflicting reports [88,112,124,169] on the room temperature carrier mobility of Cs 2 SnI 6 , the origin of conductivity in this compound has been hypothesized to stem from (a) the possession of dispersive conduction band states and (b) the presence of iodine vacancies. Cs 2 SnI 6 compound exhibits intrinsic n-type electrical conductivity and other fascinating features such as direct bandgap, air and moisture stability, and strong visible light absorption.…”
Section: Vacancy Ordered Halide Double Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sn‐based system is also a promising Pb‐free blue perovskite material. Unfortunately, the PLQYs of Sn‐based perovskite NCs (CsSnX 3 and Cs 2 SnX 6 ), are generally low due to the oxidation process from Sn (II) to Sn (IV) . Compared with Bi‐based perovskites, Sn‐based perovskites have a great deal of intrinsic defect sites.…”
Section: Component Engineering For Blue‐emissive Perovskitesmentioning
confidence: 99%
“…LEDs (Figure 2(c)), optically pumped lasers (Figure 2(d)), etc [32][33][34]. To address the toxicity issue of Pb, 3D tin halide perovskites have been developed [35][36][37][38][39]. However, bivalent Sn 2+ could be easily oxidized to Sn 4+ , resulting in the instability of the material itself and morphological change into other species [40].…”
Section: Bulk Abx 3 Metal Halide Perovskitesmentioning
confidence: 99%